Suicidality Related to the COVID-19 Lockdown in Romania: Structural Equation Modeling - Panfil, Anca-Livia; Lungeanu, Diana; Tamasan, Simona; Bredicean, Cristina; Papava, Ion; Smirnova, Daria; Fountoulakis, Konstantinos N. (Frontiers in Psychiatry, 2022)
Background: Suicidality is a serious public health concern at a global scale. Suicide itself is considered to be preventable death, thus calling for efforts to assess the risks and design effective solutions. As part of the international COMET-G study, we conducted a national level investigation to examine the individual disturbances (such as anxiety, depression, or history of life-threatening attempts) and environmental factors (such as adherence to conspiracy theories or Internet use) associated with suicidality in the Romanian adult population during the COVID-19 lockdown. Participants and methods: One thousand four hundred and forty-six adults responded to the anonymous on-line questionnaire, with mean age ± standard deviation of 47.31 ± 14.21 years (1142 females, 292 males, 12 identified as 'other'). Data were analyzed using descriptive statistics and structural equation modeling (SEM). Results: Univariate analysis showed strong and significant correlation between anxiety and depression scores, with the Spearman coefficient of R=0.776, p<0.001. Both the suicidality scores and the Internet use correlated moderately with anxiety and depression, with two-by-two Spearman coefficients between R=0.358 and R=0.355 (p<0.001 for all). Three successive SEM models were identified. Emotional disturbances, previous life-threatening attempts, and younger age proved to be significant predictors for suicidality, while the patterns of reality reading (including religious inquiries, Internet use, and beliefs in conspiracy theories) did not reach the statistical significance. Significant covariance existed between each pair of the hypothesized individual contributors to suicidality (p<0.001). There was no covariance between the Internet use and belief in conspiracy theories. Conclusion: Anxiety and depression were the leading factors in suicidality, with reality reading patterns having only a minor and indirect influence, thus calling for new strategies for assessing suicidality risks and identifying effective interventions.